VEGFD signaling balances stability and activity-dependent structural plasticity of dendrites - Aksan, Bahar; Kenkel, Ann-Kristin; Yan, Jing; Sánchez Romero, Javier; Missirlis, Dimitris; Mauceri, Daniela (Cellular and molecular life sciences, 2024)
Mature neurons have stable dendritic architecture, which is essential for the nervous system to operate correctly. The ability to undergo structural plasticity, required to support adaptive processes like memory formation, is still present in mature neurons. It is unclear what molecular and cellular processes control this delicate balance between dendritic structural plasticity and stabilization. Failures in the preservation of optimal dendrite structure due to atrophy or maladaptive plasticity result in abnormal connectivity and are associated with various neurological diseases. Vascular endothelial growth factor D (VEGFD) is critical for the maintenance of mature dendritic trees. Here, we describe how VEGFD affects the neuronal cytoskeleton and demonstrate that VEGFD exerts its effects on dendrite stabilization by influencing the actin cortex and reducing microtubule dynamics. Further, we found that during synaptic activity-induced structural plasticity VEGFD is downregulated. Our findings revealed that VEGFD, acting on its cognate receptor VEGFR3, opposes structural changes by negatively regulating dendrite growth in cultured hippocampal neurons and in vivo in the adult mouse hippocampus with consequences on memory formation. A phosphoproteomic screening identified several regulatory proteins of the cytoskeleton modulated by VEGFD. Among the actin cortex-associated proteins, we found that VEGFD induces dephosphorylation of ezrin at tyrosine 478 via activation of the striatal-enriched protein tyrosine phosphatase (STEP). Activity-triggered structural plasticity of dendrites was impaired by expression of a phospho-deficient mutant ezrin in vitro and in vivo. Thus, VEGFD governs the equilibrium between stabilization and plasticity of dendrites by acting as a molecular brake of structural remodeling.